DOP01 A multi-centre study to explore the prevalence of Inflammatory Bowel Disease indicators in patients with moderate- to- severe psoriasis: Baseline results from the EPIC study. (21st January 2022) - Hayee, B; Ghosh, S; Carter, B; Bartlett, S; Powles, E; Millward, R; Watcham, S; Blanthorn-Hazell, S; Crooks, J; Hansell, C; Millar, J; Williams, C; et al.
Abstract: Background: Evidence suggests there is an increased incidence of inflammatory bowel disease (IBD) in the psoriasis (PsO) population. However prior studies may have underestimated the degree of this association, by not considering (pre-)clinical markers or symptoms of IBD (e.g. elevated faecal calprotectin [FCal] and/or IBD red flags). Furthermore, patients with PsO are not typically screened for IBD. Here we describe the prevalence of IBD indicators in patients with moderate-to-severe PsO. Methods: This was a multi-centre UK study of adults (≥18 years) with moderate-to-severe PsO. Patients were recruited from 12 primary care practices in Greater Manchester between November 2019 – April 2021 (in total, 983 eligible patients from an original cohort of 3485 were invited to participate). Retrospective review of primary care medical records was used to confirm a prior IBD diagnosis at baseline. For patients without a confirmed diagnosis, FCal monitoring and a bespoke questionnaire derived from validated measures of gastrointestinal (GI) symptoms and IBD red flags (CalproQuest IBD and Red Flag Index) were used to screen for IBD risk. Baseline interim data are presented as observed proportions, descriptive statistics, and counts along with 95% confidence intervals (CI). Results: 252 patients were included: mean age was 57 (±15 SD) years and 54% were female (Table 1). Use of non-steroidal anti-inflammatory drug therapy was reported by 15.5% of patients. In total, 64.7% (CI: 53.4−70.6%) of patients had ≥1 indicator of IBD risk at baseline (i.e., ≥1 of: IBD diagnosis, FCal ≥50 ɥg/g or ≥1 IBD red flag) and 3.6% (CI: 1.7−6.7%) of patients had a confirmed diagnosis of IBD. At baseline, 38.1% (CI: 33.5–46.1%) of patients had elevated (≥50μg/g) FCal (Table 2), and 34.9% (CI: 30.2−42.6%) of patients reported ≥1 IBD red flag. Both elevated FCal and GI symptoms were observed in 26.2% (CI: 21.8−33.5%) of patients. Figure 1 depicts the overlap between different IBD markers in this cohort. Conclusion: The risk of IBD in patients with PsO may be higher than previously reported. While 3.6% of patients in this cohort of patients with moderate-to-severe PsO had a confirmed IBD diagnosis, approximately two-thirds of patients exhibited at least one indicator of IBD risk (FCal ≥50μg/g and/or IBD red flag[s]). This study therefore highlights a population for whom further investigation to confirm IBD may be warranted. Prospective follow-up over the next two years will report on the outcomes of investigations, the final diagnoses and treatments in the identified 'at risk' cohort.